MUGABE’S POLICY LEGACIES ON URBAN POVERTY AND INFORMALITY IN HARARE, ZIMBABWE - Logistic MAKONI; Ngoni C. SHERENI; Kevin MEARNS (Revista Română de Geografie Politică)
Zimbabwe gained independence in 1980 and had Mugabe as its first black president. Thirty-seven years later, Mugabe was, atypically, ousted from office. There exist controversies around his thirty-seven-year term. This paper evaluates Mugabe’s policy legacies on urban poverty and informality in the country’s capital city, Harare. Desktop research was used to achieve the aim of the study. Key themes that emerged show that power and intolerance were the main factors behind Mugabe’s policies and a key reason for the current levels of poverty and informality. Recommendations on urban management policies to address African urban poverty and informality were proposed.